THE EFFECTIVENESS OF MIND MAPPING TECHNIQUE IN ENHANCING STUDENTS’ READING ACHIEVEMENT - Karolina, Karolina (English Department FBS UNP, 2019)
Reading is considered challenging for high students in which students are not massively exposed to English input. Despite the challenge, the students are required to have good reading ability. One of the most proposing techniques is mind mapping. This research aims to reveal to what extent the mind mapping technique enhances students’ reading achievement. Moreover, the research was quasi-experimental research which involved one experimental groups and one control group. The samples were tenth grade students at SMAN 2 Kuala Kapuas, Central Kalimantan. Moreover, mind mapping technique served as the independent variable; while, students’ achievement in reading served as dependent variable. The findings revealed that the mind mapping technique enhances students’ reading achievement. In other words, it signifies the effectual mind mapping technique in enhancing students’ reading achievement